Severe Hyponatremia Unveiling Isolated ACTH Deficiency in Chronic Alcohol Abuse: A Diagnostic Challenge - Vassallo, Alberto (Brazilian Journal of Case Reports, 2025)
Isolated adrenocorticotropic hormone deficiency (IAD) secondary to chronic alcohol abuse is an extremely rare condition, often underdiagnosed due to nonspecific clinical features overlapping with complications of alcoholism. A 42-year-old Brazilian male with chronic alcohol abuse was admitted for hematemesis and severe hyponatremia refractory to conventional therapy. Biochemical evaluation revealed profound hypocortisolism with inappropriately low adrenocorticotropic hormone (ACTH) levels and normal pituitary function and imaging. A comprehensive workup ruled out other potential causes of hyponatremia. Diagnosis of IAD was hypothesized. Hydrocortisone replacement therapy led to rapid clinical improvement and normalization of sodium levels. This case highlights the importance of considering IAD in chronic alcoholics with unexplained hyponatremia. Early diagnosis and corticosteroid replacement therapy are essential to prevent life-threatening complications.